Active labour market policy in China since 1978: A preliminary assessment - Sonja Opper (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
The central question will be, whether ALMPs are actually in line with the transition aim of struc-tural adjustment. Due to a lack of consistent micro-level data, theoretical considerations will be an important supplement for evaluating the Chinese concept. In order to illuminate the quantitative and qualitative requirements of efficient ALMPs, the following section will first describe the development of the employment sitution in China since 1978. The third section provides an overview of the most important elements of current active employment policy in China. Special focus will be put on technical aspects, target groups and the coverage of the different instruments launched by the MoL. On the basis of these findings some tentative conclusions concerning the characteristics of Chinese employment policy and its possible contribution to structural change will be drawn.
Keywords: 330; Arbeitsmarktpolitik; China